Pregnancy and COVID-19: Study of trends in brazilian scientific production - Lima, Gabriela Colombi de; Lima, Jozéli Fernandes de; Machado, Liane Bahú; Reginaldo, Marjana Pivoto; Kleinubing, Raquel Einloft; Langendorf, Tassiane Ferreira (Seven Editora, 2023)
COVID-19 has variable symptoms, specific diagnosis, and no safe and effective treatment, in addition to prevention and vaccination measures. Among the risk groups are pregnant and puerperal women, with possible consequences for the fetus. In addition to hospitalization in the Intensive Care Unit (ICU), there is a high number of deaths classified as maternal mortality. Thus, the objective of this study is to identify the trend of Brazilian scientific production regarding pregnancy and COVID-19, with a review question: What is the trend of Brazilian dissertations and theses about pregnancy related to COVID-19? This is a narrative review of the literature, carried out in July 2022, in the theses and dissertations bank of the Higher Education Personnel Improvement Commission (CAPES) portal, with a search strategy "pregnancy AND COVID-19" and clipping temporal. As inclusion criteria, field research theses or dissertations that answered the review question and excluded studies with incomplete abstracts and/or not available in the database. In the analysis, a detailed reading was carried out with the external organization of the data, consisting of eight theses and dissertations. As for the results, six are dissertations and two theses; mostly published in 2021 and 2022; in the Southeast and Northeast regions of Brazil; through four federal universities, two state universities, and one private university. Regarding the approach, four studies were qualitative, two quantitative, and one quali-quantitative; predominating the area of Medicine, followed by Biotechnology, Dentistry, and Collective Health. There was a lack of studies produced by other areas of health sciences on the theme supported by the need for specialized and multidisciplinary care with support for doubts. Complications such as an increase in the prevalence of preeclampsia, laboratory, and vascular alterations have been identified in pregnant women with COVID-19. Thus, care strategies are needed to reduce the risk of infection, such as the development of digital technologies and the use of telehealth. In addition to clinical issues, this group suffered impacts on mental health due to social isolation and changes in maternal-fetal attachment. It concludes the vast approach that pregnancy and COVID-19 can be researched, with gaps in maternal mortality, and reinforces the potential of prevention actions to meet the Sustainable Development Goals (SDGs). DOI:https://doi.org/10.56238/emerrelcovid19-016